YIIFSWA II OPENDAY - interview with Alhaji Adigun Atunnise - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Interview and yam harvesting with Alhaji Adigun Atunnise, in Kishi, Oyo State, Nigeria. Going beyond exploring the potential of YIIFSWA-II improved varieties at Farmer's level.